The effect of magnetized seawater on physiological and biochemical properties of different rice cultivars - Ekris Sutiyanti; Diah Rachmawati (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sutiyanti E, Rachmawati D. 2021. The effect of magnetized seawater on physiological and biochemical properties of different rice cultivars. Biodiversitas 22: 3083-3091. Seawater is an alternative source to overcome the reduced availability of freshwater in agricultural practices. However, seawater cannot be used directly because it has high salinity that causes various disturbances in plant growth and development. Magnetic field treatment can be used for seawater desalination. The objective of this study was to analyze the potential of magnetized seawater for agricultural irrigation by observing the effect of magnetized seawater on physiological and biochemical properties of different rice cultivars. This research was conducted in a Completely Randomized Design (CRD) with  3 research factors, which were 2 rice cultivars ('IR 64' and 'Inpari 35'), 2 levels of salinity (0 and 10 dS m-1), and 4  types of magnetic treatment (0 untreated with magnetic device, 1, 2 and 3 cycles treated with magnetic device). Variables including plant growth (plant height, fresh weight and dry weight), physiological characters (chlorophyll content, carotenoid content, membrane stability index, relative water content, proline content) and biochemical properties (superoxide dismutase, malondialdehyde, H2O2 and anthocyanin content) were observed. Magnetized seawater 3 cycles enhanced growth, physiology and biochemical parameters of ‘IR 64’ and ‘Inpari 35’ in 0 and 10 dS m-1 level salinity with decreasing level salinity of water to minimize effect of salinity. The effect of magnetized seawater treatment is more visible to increase the growth of ‘IR 64' rice plants.